A targeted next-generation sequencing panel reveals novel mutations in Japanese patients with primary ciliary dyskinesia. Issue 3 (June 2018) - Takeuchi, Kazuhiko; Kitano, Masako; Kiyotoshi, Hiroko; Ikegami, Koji; Ogawa, Satoru; Ikejiri, Makoto; Nagao, Mizuho; Fujisawa, Takao; Nakatani, Kaname
Abstract: Objective: Primary ciliary dyskinesia (PCD) is a rare genetic disorder caused by functional impairment of cilia throughout the body. The early diagnosis of PCD is important for the prevention of long-term sequelae; however, this is often challenging because of the phenotypic heterogeneity of PCD and difficulty in genetic analysis. The majority of PCD patients in Japan are not diagnosed properly. To diagnose PCD more accurately, we developed a targeted next-generation sequencing (NGS) panel. Methods: We examined 46 patients (age range, 1–64 years; 23 male and 23 female) who were clinically suspected of PCD. First, mutation hotspots in DNAH5 and DNAI1 were sequenced by the Sanger method. Next, exome sequencing was performed in 32 known PCD genes using our novel NGS panel with the Ion Torrent PGM system. Variant annotation was generated by Ion Reporter Version 5.0 (Life Technologies). Mutations found in the panel were validated by Sanger sequencing. Results: Disease-causing gene mutations were found in 10 patients from 7 families: DNAH5 in 4 families, and DNAI1, CCDC40, and RSPH4A in 1 family each. Heterozygous mutations were found in 1 patient. The majority of the mutations found in the present analysis were novel. Conclusion: Japanese PCD patients have novel mutations in cilia-related genes. This targeted NGS panel can identify disease-causing mutations in patients with PCD.